The biological effect of the under - killer concentration of some pesticides in some domestic fly virgins - Nazar Al-Mallah; Abduljabbar Ibraheem (College of Education for Pure Sciences, 2007)
The results of the recent study revealed that the biological effect of sub-lethal concentration of some insecticides were varied on housefly eggs and pupae. The results mentioned a higher effect ofNemec-super in increasing the average incubation period and redaction of the average eggs hating percentage egg percentage which reached 20.8 hour 70.1% respectively . The Cyromazine average period of larval stage 11.2 , 10.4 days respectively and the average percentage of abnonnal larvae produced 4.5 , 5.0% respectively from treated eggs . The effect of eggs treatment expand to the average period of pupal stage and to the percentage of adult eclosion from the pupae , average period of adult stage and on reducing the number of eggs I female .Pupal treatment showed a little variation on average pupal period and percentage of adult eclosion from the pupae , adult period and number of eggs /female .